ANALISIS PERFORMA RDF DENGAN PEREKAT LIMBAH ORGANIK UNTUK MEMENUHI STANDAR MUTU INDUSTRI - Tambunan, Alvian; Prawoto, Prawoto; Hardiyanto , Catur (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
This study aims to obtain RDF adhesives made from organic waste and to determine the effect of adhesives on RDF performance. The method used in this research is the experimental method. The data analysis technique used is descriptive quantitative. The various types of adhesives used are waste banana peels, cassava peels, and cocoa peels. The ratio of the composition of RDF and adhesive waste is 9:1 mass unit. RDF material is mashed and filtered using mesh 10, after being mixed with adhesive then pressed with pressure 5; 7.5; 10; and 12.5 bar, then dried in an oven at 150 0C for 3 hours and dried in the sun for two days. RDF testing was carried out by proximate for water content and ash content, by bomb calorimeter for calorific value, and by Shore Hardness Test for hardness. The results showed that waste banana peels, cassava peels, and cocoa peels can function as RDF adhesives for organic waste and meet industry standards, replacing plastic or flour-type adhesives that have been used so far. The calorific value, moisture content, and ash content of RDF with the three adhesives were (5495.410 cal/g, 7.78%, and 16.74%) for banana peel adhesive, (6068.007 cal/g, 6.18%, and 17.14%) for cassava peel adhesive and (5,504.438 cal/g, 5.36%, and 17.19%) for cocoa shell. The results of the hardness test of RDF materials with the three adhesives each with variations in pressure showed (6 Shore D 5 bar, 8.5 Shore D 7.5 bar, 13 Shore D 10 bar, and 19 Shore D 12.5 bar) for banana peel adhesive, (6.5 Shore D 5 bar, 10 Shore D 7.5 bar, 14 Shore D 10 bar, and 20 Shore D 12.5 bar) for cassava peel adhesive and (8 Shore D 5 bar, 12 Shore D 7.5 bar, 18 Shore D 10 bar and 24 Shore D 12.5 bar) for cocoa shell adhesive.